Metode Latihan Interval (Interval Training) sebagai Upaya Meningkatkan Volume Oxigen Maximum (VO2Max) Pemain Futsal Wanita - Chaeroni, Ahmad; Rido, Muhamad; Bahtra, Ridho; Gemaini, Andri (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2023)
The interval training method is one form of exercise that is expected to increase Volume Oxigen Maximum (VO2Max), especially for female futsal players. The purpose of this study was to determine how much influence the interval training method has on increasing VO2Max for female futsal players. Method The approach in this study used the